(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Today, 2.1% of the world’s population suffers from diabetes mellitus, and in 97% of cases it is type 2 diabetes mellitus (T2DM). Type 2 diabetes develops as a result of decreased insulin secretion b- pancreatic cells and decreased sensitivity of peripheral tissues to the hormone (insulin resistance). Analysis of incidence indicates that in the next decade the contribution of type 2 diabetes to overall mortality will increase and by 2030 will be 3.3% [1, 18]. Types 1 and 2 diabetes are associated with an increased risk of developing cardiovascular disease (CVD). Mortality from coronary heart disease (CHD) in men and women with diabetes is 2–3 and 3–5 times higher, respectively, than in patients of comparable age and gender without diabetes [2]. The share of CVD in the mortality structure of patients with diabetes is 80%, so the importance of their early diagnosis and aggressive treatment should be emphasized. A number of epidemiological studies have shown that in patients with diabetes, the incidence of CVD increases as glycemia increases [3, 4].